2012
DOI: 10.1371/journal.pone.0043664
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 1, a Potential Marker for Cancer Stem Cells in Human Sarcoma

Abstract: Tumors contain a small population of cancer stem cells (CSC) proposed to be responsible for tumor maintenance and relapse. Aldehyde dehydrogenase 1 (ALDH1) activity has been used as a functional stem cell marker to isolate CSCs in different cancer types. This study used the Aldefluor® assay and fluorescence-activated cell sorting (FACS) analysis to isolate ALDH1high cells from five human sarcoma cell lines and one primary chordoma cell line. ALDH1high cells range from 0.3% (MUG-Chor1) to 4.1% (SW-1353) of gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 37 publications
1
75
0
1
Order By: Relevance
“…Furthermore, coupling the chemotherapeutic agents etoposide and cisplatin with the differentiation agent retinoic acid increased the inhibition of cell growth in U-CH1 cells, suggesting that the chemoresistance of chordomas may be a result of the presence of cancer stem cells [8]. ALDH, a common marker for cancer stem cells, was observed in a very small portion of the MUG-Chor cell line population [52].…”
Section: Cancer-stem-like Cells In Chordomasmentioning
confidence: 99%
“…Furthermore, coupling the chemotherapeutic agents etoposide and cisplatin with the differentiation agent retinoic acid increased the inhibition of cell growth in U-CH1 cells, suggesting that the chemoresistance of chordomas may be a result of the presence of cancer stem cells [8]. ALDH, a common marker for cancer stem cells, was observed in a very small portion of the MUG-Chor cell line population [52].…”
Section: Cancer-stem-like Cells In Chordomasmentioning
confidence: 99%
“…Furthermore, in solid tumors, it is possible to identify the side population (SP), characterized by the expulsion of Hoestch33342 1 dye within CSCs due to the presence of efflux pumps in these cells [12]. Aldehyde dehydrogenase 1 (ALDH1) activity has also been used as a functional stem cell marker to isolate CSCs [13].…”
Section: Introductionmentioning
confidence: 99%
“…From that point of view, MSCs can be considered as candidate TICs of SS [9]. Regarding stem cell-like cancer cell populations in SS, Terry and Nielsen reported that CD133 may mark TIC in SS [10], and Lohberger et al reported aldehyde dehydrogenase (ALDH) could be a potential marker for SS [11]. In addition, Wu et al examined three cases of primary SSs and identified a side-population (SP) group harboring properties similar to those of TICs in a synovial sarcoma [12].…”
Section: Introductionmentioning
confidence: 99%